Extraction of flavonoids from Citri Reticulatae Pericarpium Viride using a deep eutectic solvent. Issue 41 (21st September 2022) - Li, Gang; Lei, Jie; Li, Sihui; Jiang, Yongmei; Zhang, Feng; Song, Changwei; Xiao, Shiji; Fu, Shaobin; Zhou, Jinquan; Wu, Faming; Wang, Gang
Abstract : Flavonoids are the main active ingredient in Citri Reticulatae Pericarpium Viride (CRPV). Abstract : Flavonoids are the main active ingredient in Citri Reticulatae Pericarpium Viride (CRPV). In this study, a deep eutectic solvent (DES) was explored to extract the main flavonoids from CRPV, including narirutin (NAR) and hesperidin (HES). A total of 30 DESs were prepared, and DES-20 (proline : urea) was selected as the optimal solvent. According to the single factor and response surface methodology experiments, the optimal extraction conditions for the flavonoids included a molar ratio of 1 : 2, water content of 30%, extraction time of 28 min, extraction power of 240 W, and a liquid-to-solid ratio of 70 mL g −1 and the optimal extraction yields of NAR and HES were 21 ± 2 mg g −1 and 60 ± 2 mg g −1, respectively. The recovery rate of NAR and HES with macroporous resin SP825 were 88 ± 3% and 86 ± 4%, respectively. Compared with traditional extraction methods, this novel method greatly improved extraction efficiency and saved time. Scanning electron microscopy results showed that this novel method could destroy the plant cell wall to enhance the extraction efficiency. Then, 21 flavonoids were identified through an ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) technique and nine of them were discovered for the first time in CRPV extracts. Furthermore, a high-performance liquid chromatography (HPLC) method was simultaneously used to determine NAR and HES in CRPV extracts upon methodological validation. Finally, antioxidant and cytotoxic experiments in vitro showed that the flavonoids extracted from the CRPV exhibited certain antioxidant and cytotoxic activities. The above results indicated that the DES was a green solvent, which can effectively extract NAR and HES from CRPV.